Directions for using Analytical Procedures in Assessing the Financial Condition of Economic Entities - Xajimuratov Nizomjon Shukurullayevich; Yuldashev Farxodjon Maxmudjonovich (International Journal on Economics, Finance and Sustainable Development, 2022)
Methodological aspects of the application of analytical operations in audits are studied in the article. As a result of the research, proposals were developed to improve the use of analytical procedures.